UNMANNED AERIAL VEHICLE (UAV)-DRONE UNDER ROBOT OPERATING SYSTEM (ROS) FOR OBSTACLE AVOIDANCE via TAG RECOGNITION - MUHAMAD BARZANI, FADHIL (IRC, 2016)
Parrot AR.Drone 2.0 is a type of Unmanned Aerial Vehicle (UAV) that has been used widely for entertainment as starters and not long after that they started with research mainly for the application of surveillance and search and rescue mission. ROS or known as Robot Operating System is used for developing a swarm of drone that is able to make certain task via tag recognition. ROS widely used with all sort of robot application development because sensor data transmission for robot system analysis will become easy with ROS nodes and packages once the installation and compilation did correctly. ROS nodes for sensors data transmission that is able to communicate between laptop and the drone itself will be further analyzed and processed by the closed-loop control system. The developed program consisting of several packages that are aimed to demonstrate obstacle avoidance using tag recognition and convert it to certain task for example search and rescue.